The Expression of Visceral Fat Uncoupling Protein-1 is Higher in Moderate-Intensity Swimming than in Low or High-Intensity Swimming in Mice - Chabib Fachry Albar, - (Ektodermal Displazi Grubu, 2021)
To prove the effect of exercise intensity on fat browning process through increased level of muscle peroxisome proliferator-activated receptor-γ coactivator 1α (PGC-1α) and visceral fat’s uncoupling protein 1 (UCP1) expression in male mice. The research used a posttest only control group design. Mice were divided into 4 groups: K1 (control), K2 (mild-intensity swimming with 3% body weight loaded), K3 (moderate-intensity swimming with 6% body weight loaded) and K4 (high-intensity swimming with 9% body weight loaded). The intervention was carried out for four weeks, three times a week. Level of PGC-1α was measured by ELISA of gastrocnemius muscle, and visceral fats UCP1 expression measured by immunohistochemistry. There were differences level of muscle PGC-1α in K1 (1.58±0.29) pg/mL, K2 (4.71±0.31) pg/mL, K3 (5.42±0.34) pg/mL, and K4 (3.34±0.35) pg/mL with p=0.00 (p<0.05). The highest PGC-1α level was found in the group given moderate-intensity swimming (K3). Morever, there were differences of the visceral fats UCP1 expression in K1 (5.47±0.83) IRS/LP, K2 (7.23±1.57) IRS/LP, K3 (9.17±1.65) IRS/LP, and K4 (6.93±1.42) IRS/LP with p=0.00 (p<0.05). Variation of exercise intensity affects level of muscle PGC-1α and the expression of visceral fat’s UCP1 in male mice. Moderate-intensity exercise has the highest level of muscle and visceral fat UCP1 expression.